2014
DOI: 10.1155/2014/308613
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of aPleurotus ostreatusLaccase Mixture on Perlite and Its Application to Dye Decolourisation

Abstract: In the present study, a crude laccase preparation from Pleurotus ostreatus was successfully immobilized on perlite, a cheap porous silica material, and tested for Remazol Brilliant Blue R (RBBR) decolourisation in a fluidized bed recycle reactor. Results showed that RBBR decolourisation is mainly due to enzyme action despite the occurrence of dye adsorption-related enzyme inhibition. Fine tuning of immobilization conditions allowed balancing the immobilization yield and the resulting rate of decolourisation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…These catalytic behavior deviations upon immobilization are usually assigned to: (i) the stabilization of the tertiary structure of the enzyme that result from the attachment to the immobilization carrier, leading to a decrease in structure flexibility [40]; and (ii) alterations of enzyme microenvironment that improves the retention of activity at extreme pH values [41].…”
Section: Effect Of Ph and Temperature On The Catalytic Activity Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…These catalytic behavior deviations upon immobilization are usually assigned to: (i) the stabilization of the tertiary structure of the enzyme that result from the attachment to the immobilization carrier, leading to a decrease in structure flexibility [40]; and (ii) alterations of enzyme microenvironment that improves the retention of activity at extreme pH values [41].…”
Section: Effect Of Ph and Temperature On The Catalytic Activity Of Thmentioning
confidence: 99%
“…immobilization carrier, leading to a decrease in structure flexibility [40]; and (ii) alterations of enzyme microenvironment that improves the retention of activity at extreme pH values [41]. …”
Section: Effect Of Ph and Temperature On The Catalytic Activity Of Thmentioning
confidence: 99%
“…The immobilization of enzymes also provides clear advantages compared to the conventional industrial processes, where for example, continuous flow reactors make the use of laccase more cost effective. Apart from the fact that immobilized enzymes are used in the same applications as free enzymes, and with even better results, with the use of these technologies, novel application are more likely to be developed . The inconveniences experienced with the use of free enzymes have led to scientists to focus their efforts in developing new enzyme immobilization techniques whether by chemical modification or genetic modification or a mixture of these technologies .…”
Section: Chemical Modification Strategies For Laccase Improvementmentioning
confidence: 99%
“…LCBB was 25 times less expensive than a biocatalyst made by linking a laccase to Celite 633 through a two step reaction [14], and its activity was twice higher than Celite-based catalyst. Relatively to other supports, such as chitosan [16] and, very recently, Perlite [36], the price of LCBB results to be more convenient. By considering this, it was concluded that LCBB was active enough for further testing, especially because various possibilities exist to improve the specific activity of LCBB.…”
Section: Activity Of Laccase Immobilized On Clinoptilolite By Adsorptmentioning
confidence: 99%